PROFITABILITY, TUNNELLING INCENTIVES, AND BONUS MECHANISMS ON TRANSFER PRICING DECISION: AN ANALYSIS OF THE ENERGY SECTOR IN INDONESIA - Alfandia, Nurlita Sukma; Amalia, Levika Ulil (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
The research examines the effect of profitability, tunnelling incentives, and bonus mechanisms on transfer pricing decision in the energy sector. Multinational corporations often utilize transfer pricing to redistribute profits and reduce tax obligations. This study uses data from 88 observations, based on 22 energy sectors. This type of research is quantitative research with a theoretical explanation approach. Profitability is evaluated using Return on Assets (ROA), tunnelling incentives are represented by the ownership proportion of the largest shareholder, and bonus schemes are analyzed using the Net Income Trend Index. Tunnelling motivations significantly affect transfer pricing decision. Majority shareholders utilize their authority to allocate resources to related businesses, often harming smaller shareholders through transfer pricing decisions. In contrast, profitability systems and bonus mechanisms do not show substantial influence. Bonus distribution based on profits and management policies are less relevant in making transfer pricing decision in the energy industry.The results indicate that operational stability, regulatory compliance, and long-term strategy are more important than profit manipulation in energy sector companies. These results highlight the importance of incentives. There is a need for stricter regulation of related party transactions and better protection for minority shareholders to ensure transparency and equity in transfer pricing procedures.